Immunomodulation of CXCL10 Secretion by Hepatitis C Virus: Could CXCL10 Be a Prognostic Marker of Chronic Hepatitis C?. (8th August 2019) - Ferrari, Silvia Martina; Fallahi, Poupak; Ruffilli, Ilaria; Elia, Giusy; Ragusa, Francesca; Paparo, Sabrina Rosaria; Patrizio, Armando; Mazzi, Valeria; Colaci, Michele; Giuggioli, Dilia; Ferri, Clodoveo; Antonelli, Alessandro
Abstract : Chemokine (C-X-C motif) ligand (CXCL)10 and other CXCR3 chemokines are involved in the pathogenesis of acute and "chronic hepatitis C virus (HCV) infection" (CHC). Here, we review the scientific literature about HCV and CXCL10. The combination of circulating CXCL10 and single nucleotide polymorphisms (SNPs) in IL-28B can identify patients with acute HCV infection most likely to undergo spontaneous HCV clearance and those in need of early antiviral therapy. In CHC, the HCV and intrahepatic interferon- (IFN-) γ drive a raised CXCL10 expression by sinusoidal endothelium and hepatocytes, thereby inducing the recruitment of CXCR3-expressing T cells into the liver; thus, CXCL10 plays an important role in the development of necroinflammation and fibrosis. Increased CXCL10 was significantly associated with the presence of active vasculitis in HCV-associated cryoglobulinemia, or with autoimmune thyroiditis in CHC. Pretreatment CXCL10 levels are predictive of early virological response and sustained virological response (SVR) to IFN- α and ribavirin and may be useful in the evaluation of candidates for therapy. The occurrence of SNPs adjacent to IL-28B (rs12979860, rs12980275, and rs8099917), and CXCL10 below 150 pg/mL, independently predicted the first phase viral decline and rapid virological response, which in turn independently predicted SVR. Directly acting antiviral agents-mediated clearance of HCV is associated with the loss of intrahepatic immune activation by IFN- α, associated by decreased levels of CXCL10. In conclusion, CXCL10 is an important marker of HCV clearance and successful therapy in CHC patients. Whether CXCL10 is a novel therapeutic target in CHC will be evaluated.